Urban villages as living gallery: Shaping place identity with participatory art in Java, Indonesia - Ernest Irwandi; Setiawan Sabana; Andryanto Rikrik Kusmara; Tisna Sanjaya (Cogent Arts & Humanities, 2023)
Over the past decade, urban villages across Java Indonesia that used to be slums were transformed into colorful villages and have become tourist destinations. Each urban village represents their local identities by creating colorful murals, promoting local food and organized festivals which expressed their unique heritage. The participatory art projects conducted in urban villages were aimed to shape place identity. Artist and residents collaboratively developed place narration and art themes. The participatory art project helps urban village residents to reimagine their place, connect ideas with place’ history and culture. This study aims to understand how art and design are incorporated within the creation of place identity through participatory action. This study uses a qualitative approach to examine the mapping and engagement strategy applied in the creation of place identity in urban villages in Java Indonesia. Research data collected through in-depth interviews, semi-structured interviews, field observations, participant observation, photographs and visual archive documentation and supported by literature study. This article highlights several key points taken from case studies in three urban villages in Java. The findings of this study are to introduce a conceptual framework of the participatory art model for place identity formation in urban villages.